2003
DOI: 10.1080/1042819031000067747
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of T-cell Non-Hodgkin's Lymphoma and its Association with Epstein-Barr Virus in Pakistani Patients

Abstract: This study analyzes the prevalence of T-cell non-Hodgkin's lymphoma (T-NHL) in a major referral center of Pakistan and its association with Epstein-Barr virus (EBV). Ninety-two cases of T-NHL were characterized on the basis of morphology, immunohistochemistry and genetic features. The prevalence of T-NHL was 22.2% of the total NHLs diagnosed during the eight years period (1992-1999). Polymerase chain reaction (PCR) technique was used to assess T-cell clonality in paraffin-embedded tissues of known T-NHL. Ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…Under these blinded conditions, we detected IGH clones in only 6 of 74 (8%) PTCL cases, consistent with previous reports on large series of PTCL (9 to 16%). [2][3][4][5][6] By contrast, we detected IGH clones in 23 of 24 (96%) pre-B-ALL cases, and similarly high rates of detection have been reported for pre-B-ALL. 18 -20 In regard to PTCL, the frequency of IGH clonality differed significantly from our previous report, in which we detected IGH clones in 33% of AILT cases and 35% of PTCL-U cases (P Ͻ 0.004).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Under these blinded conditions, we detected IGH clones in only 6 of 74 (8%) PTCL cases, consistent with previous reports on large series of PTCL (9 to 16%). [2][3][4][5][6] By contrast, we detected IGH clones in 23 of 24 (96%) pre-B-ALL cases, and similarly high rates of detection have been reported for pre-B-ALL. 18 -20 In regard to PTCL, the frequency of IGH clonality differed significantly from our previous report, in which we detected IGH clones in 33% of AILT cases and 35% of PTCL-U cases (P Ͻ 0.004).…”
Section: Discussionmentioning
confidence: 61%
“…Although PCR-based assays for TRG typically detect clones in 80 to 90% of PTCL cases, several studies have shown that IGH clones are also detected relatively frequently (9 to 16%). [2][3][4][5][6] The detection of an IGH clone, with or without a concurrent TRG clone, complicates an already challenging diagnosis.…”
mentioning
confidence: 99%
“…In particular, studies evaluating large numbers of PTCLs by PCR show that simultaneous B-and T-cell clones occur relatively often (9 to 16%). [2][3][4][5][6] These cases, with both B-and T-cell clones, present a diagnostic dilemma for the pathologist and treating oncologist.…”
mentioning
confidence: 99%
“…In the Southeast Asian population, in which EBV-positive T-cell lymphoma is more common, Huh and colleagues [10], Jung and colleagues [11], Ko and colleagues [14], and Kim and colleagues [35] have reported 58%, 46.7%, 76%, and 50% of EBV-positive cases in the Korean adult population, respectively. Meanwhile, Noorali and colleagues [16] have observed a 55.4% EBV association in adult patients from Pakistan; Hirose and colleagues [21] a 63% EBV association in a Japanese adult series; and Agarwal and colleagues [36] a 8.7% EBV association in a T-cell anaplastic large cell lymphoma series from India. Conversely, in United States, Herling and colleagues [37] described the absence of EBV in 48 anaplastic T-cell lymphoma patients.…”
Section: Discussionmentioning
confidence: 99%